(untitled) (Research, Society and Development, 2024)
Fat grafting consists of the collection of fat through the liposuction process, and used in filling to correct soft tissue defects. It can be used in the healing process of various wounds, the one presented in this work being the lacerated wound. Skin grafting is a technique used to cover skin defects in lesions in regions that are difficult to close primarily. Its objective is to verify whether fat grafting has a better prognosis for healing than skin autograft in patients with lacerated-contusive wounds. The methodology used was an narrative bibliographical research of 10 articles referring to the topic, comparing the prognoses of the two techniques. According to some articles read, the benefits were presented in several patients, in relation to a reduction in recovery time, less morbidity and improvement in the results that were initially established.